Pandangan Masyarakat Aceh tentang Penggunaan Ganja - Muhammad Zainul Muttaqien (Syntax Corporation Indonesia, 2024)
This study aims to explore the views of the Acehnese people regarding the use of marijuana, with a special focus on the perspectives of traditional leaders and clergy in the region. Aceh, known for its strict application of sharia law, has a distinctive view of prohibited substances, including marijuana. This research method uses a qualitative approach with in-depth interview techniques with traditional leaders and clergy as well as literature studies to strengthen their views on the legality, social impact, and moral implications of cannabis use. The results of this study show that medically, marijuana can overcome long-term pain, mental health problems, slow the development of cancer cells, and improve symptoms of epilepsy and multiple sclerosis. However, there are health risks such as mental health problems, testicular cancer, and respiratory diseases if used. In Indonesia law, marijuana is considered a drug with a high addictive effect and is prohibited from use. By teaching the community and working with law enforcement, Acehnese traditional and religious leaders play an important role in preventing marijuana abuse. In general, although marijuana has potential medical benefits, marijuana use in Indonesia must continue to be controlled and restricted to prevent abuse. If the legalization of medical marijuana is discussed, the benefits and risks should be carefully considered, with strict regulation to reduce its adverse effects.